Managing anxiety in school settings : creating a survival toolkit for students - Duvall, Anna; Roddy, Crissy (New York, NY : Routledge, 2021)
"Managing Anxiety in School Settings dives into the growing topic of anxiety and its implications on students' emotional and academic wellbeing, providing key insights into how to enable students to be successful inside and outside of the classroom. This book provides the reader with a tangible set of strategies for all grade levels that can be built into individualized anxiety survival toolkits for students to utilize in a discreet and effective manner both in the classroom and in their daily lives. With real-life examples from Anxious Annie in each chapter, readers build a grounded, fine-grained understanding of anxiety's causes, different varieties, manifestations, social and learning impacts, and coping strategies. Breakdowns by grade level take into account which strategies your students will be most open to and best served by. With this book, school counselors and teachers can work with students individually, in small groups, classes, or even entire schools to create anxiety survival toolkits to provide practical strategies that help students combat their anxiety for the rest of their lives"--
OCLC-licensed vendor bibliographic record.
Keywords: School children -- Mental health; Anxiety in children -- Treatment; Anxiety in youth -- Treatment; EDUCATION / Counseling / General; PSYCHOLOGY / Psychotherapy / Counseling